Transverse response of underground cavities and pipes to incident SV waves. - Davis, C.A.
The transverse response of underground cylindrical cavities to incident SV waves is investigated. Analytical solutions are derived for unlined cavities embedded within an elastic half space using Fourier Bessel series and a convex approximation of the half space free surface. The computed displacements at the half space free surface and the tangential stresses on the cavity are compared with the results of previous investigations. The analytical solutions are extended to formulate approximate solutions for assessing hoop stresses within cavity liners impinged by low frequency waves having wavelengths much longer than the cavity diameter. The approximate solutions are compared to existing numerical solutions, and used to evaluate the dynamic response of a flexible buried pipe shaken by the 1994 Northridge earthquake. The proposed approximate model for cavity liners is useful for the seismic analysis of underground pipes and small diameter tunnels.
Keywords: Underground cavity; Buried pipes; Tunnels; Earthquake analysis